Coaching untuk Guru Membuat Modul Ajar dan Melaksanakan Pembelajaran Proyek untuk Meningkatkan Keterampilan Abad Ke-21 dan Keterampilan Literasi Murid - Cecep Maman Hermawan; Okta Rosfiani; Syamsudin; Yusup Zulfikar; Tajaufa Maulitaj Daffa (Yayasan Kawanad, 2022)
21st century skills are important for students to develop self-efficacy through problem-solving, critical thinking, collaboration, communication and creativity. A high level of 21st century skill self-efficacy is literacy. An empirical observation related to found literacy is the low literacy of teachers at a private madrasah in Bogor, West Java. For this reason, teachers are coached to create lesson her modules and conduct project learning to improve 21st century skills and student literacy. Direct instruction is a teaching strategy in which a coach (instructor) presents new knowledge or skills that can be followed by a coachee (teacher). This coaching influences the reading comprehension of teachers so that teachers acquire the skills to design, implement and assess reading comprehension in four primary reading comprehension subjects namely Science, Social Studies, Indonesian and PKN. can do. Because teachers teach reading and writing skills to students in the context of the lesson.